2010
DOI: 10.3109/17482960902822960
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance in patients with amyotrophic lateral sclerosis

Abstract: Our objectives were to analyse carbohydrate metabolism in a series of ALS patients and to examine potential association with parameters of lipid metabolism and clinical features. Glucose tolerance was assessed by the oral glucose tolerance test in 21 non-diabetic ALS patients and compared with 21 age- and sex-matched normal subjects. Lipids and lactate/pyruvate ratio, levels of pro-inflammatory cytokines (tumour necrosis factor-alpha and interleukin-6) and adipocytokines (leptin and adiponectin) were also meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 26 publications
5
100
0
Order By: Relevance
“…The results also seem to confirm early reports of abnormalities of lipid and carbohydrate metabolism in ALS patients [11][12][13]. Pradat et al [14] also recently observed an impaired glucose tolerance of ALS patients compared to controls. Jawaid et al [15] reported that diabetes mellitus was associated with a 4-year later onset of ALS.…”
Section: Discussionsupporting
confidence: 90%
“…The results also seem to confirm early reports of abnormalities of lipid and carbohydrate metabolism in ALS patients [11][12][13]. Pradat et al [14] also recently observed an impaired glucose tolerance of ALS patients compared to controls. Jawaid et al [15] reported that diabetes mellitus was associated with a 4-year later onset of ALS.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of reduced body fat mass (FM) in ALS patients [128] and reduced adipose tissue accumulation in animal models of ALS [17] have sparked the hypothesis that there is altered lipolysis in ALS. This is supported by the finding of elevated plasma FFA in patients with ALS [113,115] as well as an increased rate of lipolysis [129] and reduced FFA uptake and storage [17] in animal models. In addition to accelerated lipolysis, there is evidence to suggest that the use of glycogen (an important alternative fuel reserve stored in liver and skeletal muscle which yields glucose molecules) is decreased in ALS.…”
Section: Meeting Energy Needs In Alssupporting
confidence: 63%
“…Since the 1960s, there have been reports of impaired glucose tolerance and insulin resistance in ALS [9,11,109,110,111,112,113]. The possibility of impaired function of insulin is of particular interest in ALS because reduced glucose availability could exacerbate neuronal dysfunction, particularly in the CNS, which relies predominantly on glucose as fuel.…”
Section: Meeting Energy Needs In Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside other metabolic features, augmenting glucose intolerance is considered a sign of deteriorating and dysregulated metabolic homeostasis progressing along with the disease (66,72). Interestingly, recent research has identified miR-206's involvement in the downregulation of enzymes involved in metabolism.…”
Section: Mir-206 As a Bridge Between Alsinduced Nmj Degeneration And mentioning
confidence: 99%